Emergency psychiatry - Nicholls, Kevin (RCPsych Publications, 2015)
Emergency psychiatry is a broad field, covering situations in which a psychiatric problem, if untreated, could cause immediate harm to the patient or others. This book is a valuable, in-depth resource that is robustly rooted in clinical practice. Engaging and readable, it explores in practical detail topics often excluded from mainstream texts. Each chapter is written by an experienced clinician from that specialty. Topics covered include emergencies in child and adolescent psychiatry, violence and aggression, suicide risk, situations involving substance misuse, emergencies in liaison psychiatry, acute side-effects of antipsychotics, perinatal psychiatric emergencies. This is a useful resource for all junior doctors (especially core psychiatric trainees), nurses and multi-disciplinary healthcare professionals.